Speech Act Analysis in The Lion King (2019) Film - Ida Ayu Agung Trisna Ambara Patni (STKIP AGAMA HINDU SINGARAJA, 2023)
This research aimed to find out the locutionary act, illocutionary act, and perlocutionary act in film entitled The Lion King (2019). Speech act is one theory which is used in learning discourse analysis. Speech act divides into three types, namely; locutionary act, illocutionary act, and perlocutionary act. The locutionary act is how language is communicated like what they have been said (true meaning). The illocutionary act is how language is communicated by the utterance, but it has a hidden meaning (there are another meaning behind the true meaning). And the last is perlocutionary act, is how the language speak by an action as a result of locutionary and illocutionary act. The method that was used in this research was a qualitative descriptive method due to the author explained this research in description analysis or called the text analysis by using words. The author chose this film because this film was popular in 2019 and there were more than one speech acts that was reflected in this film. This film also can be watched with anyone in all ages (there is no limitation for the viewer of the film). As the result, the author found that there were 42 speech acts that was found by the author from The Lion King film. There were 14 locutionary acts, 14 illocutionary acts, and also 14 perlocutionary acts.